Two new species of Perymenium (Compositae-Heliantheae) from the arid part of the state of Queretaro (México) - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2010)
Perymenium arriagae and P. sotoarenasii are described and illustrated as new species from central Queretaro. Both are shrubs of xerophilous habitat and habit, and are known from scarce collections, in spite of the fact that the area has been fairly intensively explored. Seemingly the two species are closely related to each other, although they conspicuously differ in the leaf margin and leaf base, as well as in the size of the involucres and in the color of the pales. Given the imperfect stage of taxonomic knowledge of the genus, it is difficult to define their relationships with any of the remaining groups of Perymenium.